Screenplay : the foundations of screenwriting - Field, Syd (Delta Trade Paperbacks, 2005)
A generation of screenwriters has used Syd Field's bestselling books to ignite successful careers in film. Now the celebrated producer/lecturer/teacher has updated his classic guide for a new generation of filmmakers, offering a fresh insider's perspective on the film industry today. From concept to character, from opening scene to finished script, here are easily understood guidelines to help aspiring screenwriters--from novices to practiced writers--hone their craft. Filled with updated material--including all-new anecdotes and insights, guidelines on marketing and collaboration, plus analyses of recent films--Screenplay presents a step-by-step, comprehensive technique for writing the screenplay that will succeed in Hollywood.--From publisher description.